Inactivation of Salmonella enterica by UV-C Light Alone and in Combination with Mild Temperatures - Gayán, E. (American Society for Microbiology, 2012)
The aim of this investigation was to study the efficacy of the combined processes of UV light and mild temperatures for the inactivation of Salmonella enterica subsp. enterica and to explore the mechanism of inactivation. The doses to inactivate the 99.99% (4D) of the initial population ranged from 18.03 (Salmonella enterica serovar Typhimurium STCC 878) to 12.75 J ml(−1) (Salmonella enterica serovar Enteritidis ATCC 13076). The pH and water activity of the treatment medium did not change the UV tolerance, but it decreased exponentially by increasing the absorption coefficient. An inactivating synergistic effect was observed by applying simultaneous UV light and heat treatment (UV-H). A less synergistic effect was observed by applying UV light first and heat subsequently. UV did not damage cell envelopes, but the number of injured cells was higher after a UV-H treatment than after heating. The synergistic effect observed by combining simultaneous UV and heat treatment opens the possibility to design combined treatments for pasteurization of liquid food with high UV absorptivity, such as fruit juices.